Regulatory Roles of Drosophila Insulin-Like Peptide 1 (DILP1) in Metabolism Differ in Pupal and Adult Stages - Liao, Sifang; Post, Stephanie; Lehmann, Philipp; Veenstra, Jan A.; Tatar, Marc; Nässel, Dick R. (Frontiers in Endocrinology, 2020)
The insulin/IGF-signaling pathway is central in control of nutrient-dependent growth during development, and in adult physiology and longevity. Eight insulin-like peptides (DILP1-8) have been identified in Drosophila and several of these are known to regulate growth, metabolism, reproduction, stress responses and lifespan. However, the functional role of DILP1 is far from understood. Previous work has shown that dilp1/DILP1 is transiently expressed mainly during the pupal stage and the first days of adult life. Here we study the role of dilp1 in the pupa, as well as in first week of adult life, and make some comparisons to dilp6 that displays a similar pupal expression profile, but is expressed in fat body rather than brain neurosecretory cells. We show that mutation of dilp1 diminishes organismal weight during pupal development, whereas overexpression increases it, similar to dilp6 manipulations. No growth effects of dilp1 or dilp6 manipulations were detected during larval development. We next show that dilp1 and dilp6 increase metabolic rate in the late pupa and promote lipids as the primary source of catabolic energy. Effects of dilp1 manipulations can also be seen in the adult fly. In newly eclosed female flies, survival during starvation is strongly diminished in dilp1 mutants, but not in dilp2 and dilp1-dilp2 mutants, whereas in older flies only the double mutants display reduced starvation resistance. Starvation resistance is not affected in male dilp1 mutant flies, suggesting a sex dimorphism in dilp1 function. Overexpression of dilp1 also decreases survival during starvation in female flies and increases egg laying and decreases egg to pupal viability. In conclusion, dilp1 and dilp6 overexpression promotes metabolism and growth of adult tissues during the pupal stage, likely by utilization of stored lipids. Some of the effects of the dilp1 manipulations may carry over from the pupa to affect physiology in young adults, but our data also suggest that dilp1 signaling is important in metabolism and stress resistance in the adult stage.